Книга джунглей - Киплинг Джозеф Редьяpд (Шедевры мировой литературы, 2010)
Экземпляры: ф.16 (20200728) / Инвентарный номер: 60113 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: К 42 / ГРНТИ: 17.82.30 / ББК: 84(7Вел)-4